Partia Razem w prasie opiniotwórczej przed wyborami parlamentarnymi w 2015 roku - Mazur, Marek (Polityka i Społeczeństwo, 2020)
The main goal of the article concerning the parliamentary election in 2015 in Poland was to study the way the quality press presented the Razem/Together Party in the election campaign, the least (in terms of social support) the national electoral committee. Based on content analysis of Gazeta Wyborcza and Rzeczpospolita considering exposure, forms, context and themes of the party presentation there were some conclusions presented referring to the qualities of the presentation in the light of the media functions resulting from the liberal democratic model.